THE VALIDITY OF FOUR-TIER’S MISCONCEPTION DIAGNOSTIC TEST FOR DYNAMIC FLUID CONCEPTS - MENIK KURNIAWATI, DYAH; ULFAH ERMAWATI, FRIDA (Inovasi Pendidikan Fisika, 2019)
Physics was considered by students as the most difficult lesson. One of the reasons is that Physics contains many formulas without being followed by a good explanation of the Physics concepts behind the formulas from the teacher. Such situation potentially causes misconceptions to students. This paper reports the work to develop a four-tier misconception diagnostic test instrument in Dynamic Fluid concepts. The aim was to determine the feasibility of the developed instrument in terms of validity and reliability. The instrument?s validation result was obtained after two independent Physics Lecturers evaluated the content of the instrument. The reliability results was gathered from the test trial to 50 numbers of 11 grade students in Science class of senior high school 1 Sidoarjo. The results show that the validity was 92.55 %. The false positive and false negative values were 4.3% and 3.8%, respectively which means that the instrument is valid because the values less than 10 %. The correlation coefficient of Pearson product moment ( ) was 0.591 while the reliability index value ( ) was 0.751. Those values are greater than the rtable of 0.279, which means that the developed instrument is reliable. Keywords: Dynamic fluid concepts, four-tier diagnostic test, validity, reliability